Talent, Career Choice and Competition: The Gender Wage Gap at the Top - Fredrik Heyman; Pehr-Johan Norbäck; Lars Persson (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We propose a management career model where females face a gender-specific career hurdle. We show that female managers will, on average, be more skilled than male managers, since females from the low end of the talent distribution will abstain from investing in a career as a manager. The average female manager will then be better at mitigating more intense product market competition. When the intensity of product market competition increases, hirings and wages for female managers will therefore increase relative to those of male managers. Using Swedish matched employer-employee data, we find strong empirical evidence for all these predictions.
Keywords: J70; L20; M50; 330; career; gender wage-gap; job inflexibility; management; competition